Acute iris toxicity following bilateral gel stent implantation with mitomycin-C and intracameral moxifloxacin January consultation. Issue 1 (January 2022) - Liaboe, Chase; Samuelson, Thomas W.
Abstract : A 72-year-old woman presenting with moderate primary open-angle glaucoma was referred for management of glaucoma and photophobia. Abstract : A 72-year-old woman with moderate primary open-angle glaucoma was referred for management of her glaucoma and photophobia. Her ocular history is significant for routine cataract surgery in both eyes 6 years prior to presentation. She was diagnosed with glaucoma 7 months prior to presentation at which time the patient underwent sequential, ab externo, open conjunctival, Xen Gel Stent (Allergan, Inc.) placement with mitomycin-C (MMC) in each eye, approximately 2 weeks apart. The history obtained directly from the surgeon revealed that MMC dosing was 0.2 mL in a concentration of 0.2 mg/mL delivered through subconjunctival injection after placement of the gel stent. Intracameral moxifloxacin was injected at the time of surgery, and moxifloxacin and Maxitrol eyedrops were used in the postoperative period. The patient noted that, approximately 1 month after each surgery, she developed significant photophobia. An outside examination noted bilateral tonic pupils and concern for early bleb failure in the left eye. 2 months after the initial gel stent placement in the left eye, she underwent a bleb revision with a McCannel suture iris cerclage in the left eye. The intraocular pressure (IOP) in both eyes remained well controlled off pressure-lowering medications; however, the tonic pupils and photophobia persisted. The patient was subsequently referred for further assessment. At presentation, the patient's corrected distance visual acuity was 20/20 in each eye. Applanation tonometry IOP was 17 mm Hg and 14 mm Hg for the right and left eyes, respectively. Pupils were tonic and irregular. The lack of pupillary response prevented testing for relative afferent pupillary defects directly or by reverse testing. Slitlamp examination of the right eye was notable for a minimally elevated superior bleb and severe iris stromal atrophy with diffuse transillumination defects. The intraocular lens (IOL) appeared well positioned in the capsular bag without signs of pseudophacodonesis (Figure 1 ). The left eye was notable for a diffuse superior bleb and similar iris and IOL findings to the right eye, except for 2 McCannel iris sutures in the iris stroma (Figure 2 ). In both eyes, the anterior chambers were deep and quiet, and there were no corneal endothelial abnormalities. Fundus examinations of both the right and left eyes were notable for glaucomatous-appearing optic nerves and otherwise healthy macula, vessels, and periphery. Gonioscopy revealed open angles in each eye with fairly marked, densely layered pigment throughout the inferior angle and trabecular meshwork. The gel stents were positioned just anteriorly to the trabecular meshwork superiorly, well away from iris tissue. Optical coherence tomography (OCT) of the nerve fiber layer (NFL) showed moderate to severe thinning inferiorly and superiorly in the right eye, with mild to moderate thinning inferiorly in the left eye (Supplemental Figure 1, http://links.lww.com/JRS/A510 ). Ganglion cell analysis correlated with the NFL findings (Supplemental Figure 2, http://links.lww.com/JRS/A510 ). Humphrey visual field testing revealed a dense superior arcuate in the right eye and moderate inferior arcuate in the left eye (Supplemental Figures 3 and 4, http://links.lww.com/JRS/A510 ). OCT of the macula in both eyes was unremarkable. Finally, specular microscopy showed normal endothelial density and configuration of each eye (Supplemental Figure 5, http://links.lww.com/JRS/A510 ). What part of the patient's ocular history would you consider relevant to the development of tonic, atrophic pupils? What additional information would you want to know to help refine your differential diagnosis? What is your preferred surgical technique when implanting the Xen Gel Stent? Please include whether ab interno or ab externo and open or closed conjunctival approach to be used and mention antifibrosis dosing and method of administration. Finally, what would be your approach for managing this patient's severe photophobia, in the setting of her moderate open-angle glaucoma?